Contents of elements in traces in the hair of various population groups in Кavadarci as indicator of the aero pollution - Boev, Ivan; Šorša, Ajka (Geologica Macedonica, 2014)
In the paper the research of the contents of the elements in traces from the hair of various population groups in the town of Kavadarci are presented. They are determined by application of the methods ICP-AES and ICP-MS in untreated (non-washed) and treated (washed) hair. The research of the presence of the elements in traces in non-washed and washed hair are made in order to obtain results which refer to the aero pollution in the town of Kavadarci. The following concentrations of elements in traces (average values in ppm) in washed hair are obtained: (Li – 0.109; Be – 0.002; B – 2.3; Na – 35; Mg – 24; Al – 14; P – 116; K – 33; Ca – 27.4; Ti – 1.14; V – 0.0.59; Cr – 0.31; Mn – 0.50; Fe – 18; Co – 0.02; Ni – 0.78; Cu – 8.1; Zn – 133; Ga – 0.04; Ge – 0.03; As – 0.053; Sr – 0.51; Mo – 0.052; Pd – 0.004; Ag – 0.043; Cd – 0.036; Sn – 0.136; Sb – 0.031; Ba – 0.60; Tl – 0.002; Pb – 1.09; Bi – 0.005; Th – 0.005; U – 0.011); in non-washed hair: (Li – 0.196; Be – 0.009; B – 94.7; Na – 1657; Mg – 347; Al – 314; P – 164; K – 912; Ca – 1793; Ti – 17.7; V – 0.47; Cr – 1.73; Mn – 18; Fe – 164; Co – 0.218; Ni – 12.4; Cu – 13; Zn – 269; Ga – 0.55; Ge – 0.097; As – 0.22; Sr – 4.6; Mo – 0.21; Pd – 0.012; Ag – 0.106; Cd – 0.129; Sn – 1.04; Sb – 0.149; Ba – 6.9; T l– 0.007; Pb – 4.0; Bi – 0.029; Th – 0.062; U – 0.047). From the presented results it could be concluded that the contents of the elements in traces in non-washed hair is exceptionally high compared to the contents of elements in traces in washed hair. This increases in the concentration of elements in traces in non-washed/washed hair are in the interval of 1.6–47.3 times depending on the element. From the conducted research it could be concluded that the aero pollution in the town of Kavadarci has a great impact over the concentration of elements in traces in non-washed hair in the various population groups in the town of Kavadarci. Key words: hair; Kavadarci; geochemical trace elements